Design, Synthesis, and Biological Evaluation of Novel 3-Cyanopyridone/Pyrazoline Hybrids as Potential Apoptotic Antiproliferative Agents Targeting EGFR/BRAFV600E Inhibitory Pathways - Lamya H. Al-Wahaibi; Hesham A. Abou-Zied; Mohamed Hisham; Eman A. M. Beshr; Bahaa G. M. Youssif; Stefan Bräse; Alaa M. Hayallah; Mohamed Abdel-Aziz (Molecules, 2023)
A series of novel 3-cyanopyridone/pyrazoline hybrids (21–30) exhibiting dual inhibition against EGFR and BRAFV600E has been developed. The synthesized target compounds were tested in vitro against four cancer cell lines. Compounds 28 and 30 demonstrated remarkable antiproliferative activity, boasting GI50 values of 27 nM and 25 nM, respectively. These hybrids exhibited dual inhibitory effects on both EGFR and BRAFV600E pathways. Compounds 28 and 30, akin to Erlotinib, displayed promising anticancer potential. Compound 30 emerged as the most potent inhibitor against cancer cell proliferation and BRAFV600E. Notably, both compounds 28 and 30 induced apoptosis by elevating levels of caspase-3 and -8 and Bax, while downregulating the antiapoptotic Bcl2 protein. Molecular docking studies confirmed the potential of compounds 28 and 30 to act as dual EGFR/BRAFV600E inhibitors. Furthermore, in silico ADMET prediction indicated that most synthesized 3-cyanopyridone/pyrazoline hybrids exhibit low toxicity and minimal adverse effects.